2016
DOI: 10.1186/s12936-016-1557-2
|View full text |Cite
|
Sign up to set email alerts
|

Multi-dimensional knowledge of malaria among Nigerian caregivers: implications for insecticide-treated net use by children

Abstract: BackgroundPoor malaria knowledge can negatively impact malaria control programmes. This study evaluates knowledge distribution in the domains of causation, transmission, vulnerability, symptoms, and treatment of malaria. It assesses the association between a caregiver’s knowledge about malaria and ownership and use of insecticide-treated nets (ITNs) by children.MethodsSome 1939 caregivers of young children were recruited through a school-based survey in two Nigerian states. A 20-item, multi-dimensional survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 44 publications
7
13
0
Order By: Relevance
“…With behavior-driven factors; the current study identified knowledge, family supports, and self-efficacy as factors influencing the use of ITNs among school children which is consistent with that of previous studies (22). (37).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…With behavior-driven factors; the current study identified knowledge, family supports, and self-efficacy as factors influencing the use of ITNs among school children which is consistent with that of previous studies (22). (37).…”
Section: Discussionsupporting
confidence: 89%
“…Access to more than one ITN per two persons in the household independently predicted the use of ITN in this study. A similar finding was reported from a previous school-based study in that ownership was found as the main predictor of ITN use (37). This is in fact; access alone can't guarantee the ITN of use among school children.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Despite the effectiveness of these interventions, the burden of malaria in poor, rural African communities remains high [ 2 ]. A combination of poor health systems, limited access to malaria prevention, diagnosis and treatment services, poverty, and low levels of education, hinder efforts to reduce malaria in most rural African communities [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%